Pengembangan Skenario Pembelajaran Ekonomi Pancasila Berbasis Proyek melalui Metode Experiential Learning - M. Thoha Ainun N; Mit Witjaksono; Hari Wahyono (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of the development of Pancasila economic learning scenario are (1) the systematic learning process with the change of knowledge, attitudes and skills of the participants in Pancasila and the 1945 Constitution article 33 and (2) Developing activities as the basis of learning and daily life process based on Pancasila and the 1945 Constitution article 33 involves interaction, real learning outcomes and lessons learned in project activities. This research uses a qualitative approach with design based research (DBR) method. Data were collected by document analysis, interview through (FGI), and group discussions through FGD. The results of developing economic learning scenarios are (1) creating an atmosphere of economic learning based on Pancasila and the 1945 Constitution article 33 and (2) creation of economic learning results that change the knowledge, attitude, and skill. Abstrak: Tujuan dari pengembangan skenario pembelajaran ekonomi pancasila adalah (1) mengubah pengetahuan/cara berpikir, sikap, dan keterampilan peserta didik berlandaskan Pancasila dan UUD 1945 pasal 33 dan (2) pengembangan kegiatan eksperimen sebagai pendekatan pembelajaran dan proses praktik ekonomi dalam kehidupan sehari-hari yang berdasarkan Pancasila dan UUD 1945 pasal 33, meliputi interaksi pembelajaran, hasil belajar nyata, dan evaluasi pembelajaran yang diwadahi dalam kegiatan proyek. Pendekatan penelitian ini menggunakan kualitatif dengan metode Design Based Research (DBR). Data dikumpulkan dengan analisis dokumen, observasi, wawancara melalui FGI, dan diskusi kelompok melalui FGD. Hasil pengembangan skenario pembelajaran ekonomi adalah (1) menciptakan suasana belajar ekonomi yang berlandaskan Pancasila dan UUD 1945 pasal 33 dan (2) penciptaan hasil belajar ekonomi yang mengubah pengetahuan, sikap, dan keterampilan.